Neural Networks - Bishop, Christopher (Bullock, A. and Trombley, S. (Eds.) Fontana Dictionary of Modern Thought (Third ed.), 1997)
A fully revised and updated edition of this unique, well-established, classic work of reference and companion to all fields of modern thought. First published in Fontana paperback in 1977; second revised edition published in Fontana paperback in 1988; the third substantially revised edition made its first ever appearance in hardback in 1999. The Fontana Dictionary of Modern Thought has been continuously in print in earlier editions for more than twenty years. The New Fontana Dictionary of Modern Thought contains some 4000 entries by 326 expert contributors. Nearly 1000 entries are entirely new; and most of those that survive from the previous (1988) edition have been substantially revised or newly written for this edition. Areas which have been expanded include computing, identity politics and environmental studies, and there are new entries on God, communitarianism, perestroika, new world order, afrocentricity, ebonics, third wave feminism, hypertext, virtual reality, culture jamming, cloning, post-colonialism, fuzzy logic, artificial life, paper architecture, infopreneur!